IMPLEMENTASI KEBIJAKAN PELATIHAN VOKASI DALAM MENURUNKAN ANGKA PENGANGGURAN TERBUKA DI KOTA PONTIANAK PROVINSI KALIMANTAN BARAT - Teguh Anugrah Prananda; Serly Wulandari (Fakultas Politik Pemerintahan IPDN, 2026)
Open unemployment is a critical issue facing the Pontianak City Government. Despite the implementation of various training programs, the city's unemployment rate remains high. This study aims to identify and analyze the key factors influencing the successful implementation of vocational training policies in reducing open unemployment in Pontianak City, as well as to identify the obstacles involved. A qualitative descriptive approach was employed, utilizing data collection techniques such as interviews, observation, and document analysis. Data analysis involved data condensation, data presentation, and conclusion drawing. Informants were selected using purposive and snowball sampling techniques. Research findings indicate that the implementation of the vocational training program in Pontianak City has not yet been optimal. The implementation of vocational training programs in Pontianak City has not yet achieved optimal success. While policy instruments such as subsidies and digital information are utilized, they are constrained by budget limitations and digital literacy issues. Policy and institutional designs are generally sound, featuring solid coordination and improved training facilities, although performance tracking remains limited. Oversight is conducted through official bodies and community participation. Administrative capacity is rated positively, despite budgetary instability. Social acceptance is favorable, characterized by active participation and tangible benefits. Major obstacles include a lack of information and outreach, unstable budget allocations, and low job placement rates for training alumni. Keywords: Policy Implementation, Vocational Training, Open Unemployment